Transforming wound care: the role of AI in achieving clinical and financial outcomes - Jackie Stephen Haynes; James Burford (British Journal of Community Nursing, 2026)
Wound care has significant associated challenges in clinical practice, particularly for chronic wounds such as venous leg ulceration, pressure ulceration and diabetic foot ulceration. This article discusses the emerging and current applications of artificial intelligence in wound care, including wound image analysis, infection detection, predictive modelling and decision support systems. The article explores how artificial intelligence technologies are being leveraged to enhance accuracy and efficiency in wound assessment and management. Additionally, the integration of artificial intelligence with mobile health platforms and wearable devices is examined, particularly in the context of telehealth and remote patient monitoring. Consideration is given to the challenges of artificial intelligence including data quality, algorithm bias, ethical concerns and regulatory challenges. Clinicians may be able to apply artificial intelligence safely and effectively to their own clinical practice. Direction for future research is also identified.